Health concerns of lambs fed cottonseed hulls combined with chitosan by examining the blood metabolic profile and histopathology of the kidney, liver, and rumen - T Silva Magalhaes; Carvalho GGP; Santos EM; Lima AES; Freitas Junior JE; Pina DS; Santos SA; Pinto LFB; Mourao GB; Soares FDS; Pereira TCJ; Leite LC (Veterinární Medicína, 2021)
This study analysed the effect of cottonseed hulls and chitosan in diets for lambs by determining the blood metabolite profile, and the histopathology of the kidney, liver, and rumen. Eighty non-castrated Santa Inês lambs, approximately 120 days of age and a mean initial body weight (b.w.) of 22.6 (standard deviation ± 2.2 kg) were assigned to a completely randomised design, with a 2 × 2 factorial arrangement. Two chitosan levels and two cottonseed forms were evaluated. The experimental diets were following: diet containing whole cottonseed hulls (WC) without the addition of chitosan; diet containing WC with 136 mg/kg b.w. chitosan added; diet containing ground cottonseed hulls (GC) without the addition of chitosan; diet containing GC with 136 mg/kg b.w. chitosan added. The blood metabolites and hepatic enzymes ALT, AST, GGT were not significantly influenced in the treatment groups, except for the serum cholesterol concentration which was lower (P < 0.05) when the chitosan was combined with the whole cottonseed hulls. There were histopathological alterations (P < 0.05) in the liver and kidney tissue and moderate changes in the rumen samples in the animals fed cottonseed without chitosan, however, when chitosan was added, the changes were less marked. The combination of chitosan with cottonseed hulls (ground or whole) can be supplied safely to feedlot finishing lambs without compromising their health.